Logodiversity and Translation - Aubert, Francis (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThe author defines logodiversity as an affinity between biodiversity and linguistic and cultural diversity. He looks at translation as both an instrument for the preservation of logo-diversity and as a contributing factor to the silencing of human polyphony.